2022
DOI: 10.1038/s41416-022-01918-z
|View full text |Cite
|
Sign up to set email alerts
|

Applying a genetic risk score for prostate cancer to men with lower urinary tract symptoms in primary care to predict prostate cancer diagnosis: a cohort study in the UK Biobank

Abstract: Background Prostate cancer is highly heritable, with >250 common variants associated in genome-wide association studies. It commonly presents with non-specific lower urinary tract symptoms that are frequently associated with benign conditions. Methods Cohort study using UK Biobank data linked to primary care records. Participants were men with a record showing a general practice consultation for a lower urinary tract symptom. The outcome measure was pro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…A recent study showed that a prostate cancer GRS could improve risk stratification in primary care. 8 …”
Section: Genetic Risk Scoresmentioning
confidence: 99%
“…A recent study showed that a prostate cancer GRS could improve risk stratification in primary care. 8 …”
Section: Genetic Risk Scoresmentioning
confidence: 99%
“…A recent large study of white European‐ancestry (EUR) individuals in the UK Biobank showed the utility of a prostate cancer genetic risk score for triaging patients in primary care. Men in the highest quintile of risk had a prostate cancer incidence of 8.1% and could be fast‐tracked for further investigation, while the incidence among those in the lowest risk quintile was < 1% and they could more safely avoid invasive investigation [16]. Thus, there currently are clinical applications of PRS to differentiate individuals based on their genetic risk for a disease.…”
Section: Introductionmentioning
confidence: 99%
“…Polygenic risk scores (PRS), calculated by summing the effects of genetic variants across the genome, can reflect an individual's aggregate genetic liability for a particular trait or disorder. The effects of PRS, if large enough, could be useful clinically 33,34,35 . We therefore also examined PRS for M/ADs and SD as moderators of the direct and indirect effects of ACEs in both models.…”
Section: Introductionmentioning
confidence: 99%